Contrasting Patterns of Demography and Population Viability Among Gopher Tortoise Populations in Alabama. Issue 4 (8th February 2021) - Folt, Brian; Goessling, Jeffrey M.; Tucker, Anna; Guyer, Craig; Hermann, Sharon; Shelton‐Nix, Ericha; M Gowan, Conor
ABSTRACT: Population viability analyses are useful tools to predict abundance and extinction risk for imperiled species. In southeastern North America, the federally threatened gopher tortoise ( Gopherus polyphemus ) is a keystone species in the diverse and imperiled longleaf pine ( Pinus palustris ) ecosystem, and researchers have suggested that tortoise populations are declining and characterized by high extinction risk. We report results from a 30‐year demographic study of gopher tortoises in southern Alabama (1991–2020), where 3 populations have been stable and 3 others have declined. To better understand the demographic vital rates associated with stable and declining tortoise populations, we used a multi‐state hierarchical mark‐recapture model to estimate sex‐ and stage‐specific patterns of demographic vital rates at each population. We then built a predictive population model to project population dynamics and evaluate extinction risk in a population viability context. Population structure did not change significantly in stable populations, but juveniles became less abundant in declining populations over 30 years. Apparent survival varied by age, sex, and site; adults had higher survival than juveniles, but female survival was substantially lower in declining populations than in stable ones. Using simulations, we predicted that stable populations with high female survival would persist over the next 100 years but sites with lower female survival would decline, become male‐biased, and be at high risk of extirpation. Stable populations were most sensitive to changes in apparent survival of adult females. Because local populations varied greatly in vital rates, our analysis improves upon previous demographic models for northern populations of gopher tortoises by accounting for population‐level variation in demographic patterns and, counter to previous model predictions, suggests that small tortoise populations can persist when habitat is managed effectively. © 2021 The Wildlife Society. Abstract : Small gopher tortoise populations (10–50 individuals) may be stable and persist with low extinction risk if adult female survival is sufficiently high (≥0.95).